Assessment of Cotinine Reveals a Dose-Dependent Effect of Smoking Exposure on Long-term Outcomes After Renal Transplantation. Issue 9 (September 2015) - Hellemons, Merel E.; Sanders, Jan-Stephan F.; Seelen, Marc A. J.; Gans, Rijk O. B.; Muller Kobold, Anneke C.; van Son, Willem J.; Postmus, Douwe; Navis, Gerjan J.; Bakker, Stephan J. L.
<x xml:space="preserve">Abstract</x> Background Smoking is a risk factor for poor late outcomes in renal transplant recipients (RTR). Smoking exposure can be assessed by self-report and cotinine measurements. We investigated1 whether use of cotinine as a biomarker for smoking exposure can serve as an alternative for self-report and2 to compare associations of smoking exposure by self-report and cotinine with outcomes in RTR and assess dose dependency. Methods Renal transplant recipients were classified as never, former, light (⩽10 cigarettes/day), and heavy smokers (>10 cigarettes/day) according to self-report and analogous categories for urine and plasma cotinine. First, we assessed agreement of self-reported smoking exposure with smoking exposure according urine and plasma cotinine. Second, we compared the associations with graft failure and mortality. Results Of 603 RTR (age 51.5 ± 12.1 years, 55% men), 36.0% RTR were never, 42.3% former, 10.6% light, and 11.1% heavy smokers according to self-report. The majority (98.6%) of never smokers had nondetectable cotinine. However, 14 and 13 RTR reporting no active smoking had respective urine or plasma cotinine consistent with active smoking. Cotinine-based measurements were dose-dependently associated with mortality and graft failure. Conclusions Plasma and urine cotinine can serve as an alternative to self-report and were dose-dependently associated with poor late outcomes in RTR.